KONSEP HALAL HARAM DALAM EKONOMI ISLAM - Nurjaijah Lingga; Malahayatie Malahayatie (Institut Agama Islam K.H. Sufyan Tsauri, 2024)
In the context of growing globalization, understanding the concepts of halal and haram in Islamic economics is crucial. This concept functions as a guide to determine the legality of actions and reflects the moral and ethical values ​​in Islamic teachings. Halal means “permitted” and haram means “prohibited,” both of which underlie Muslims' economic decisions. The main sources of this concept are the Koran and Hadith, but its application is increasingly complex along with innovations in financial instruments and market developments. This type of research is library research with a qualitative approach. This research pays more attention to the concepts of halal and haram in the lives of Muslims which are clearly outlined in the Naqli proposition. The research results show that Islam teaches that the rules of halal (mubah) and haram are not determined by the needs of individuals or society. Halal has become an integral part of the value framework in Islamic science, functioning as a guideline that directs the behavior of the community. Thus, it can be concluded that halal philosophy includes several aspects. From an ontological perspective, halal is related to understanding the nature of something. From an epistemological perspective, halal rules are related to efforts to understand Islam correctly through a proper study process. This includes efforts or